Clinical Remission Trajectories Beyond 12 Months in Severe Asthma Patients Continuing a Single Biologic: A Real-World Single SANI Center Cohort - Simone Negrini; Stefania Nicola; Francesco Sardanapoli; Rocco Francesco Rinaldo; Marco Russo; Iuliana Badiu; Anna Quinternetto; Luca Lo Sardo; Francesco Blasi; Pierluigi Paggiaro; Enrico Heffler; Giovanni Rolla; et al. (Medical Sciences, 2026)
Background: Clinical remission is an emerging therapeutic goal in severe asthma treated with biologics. However, remission may evolve beyond the conventional 12-month assessment, and limited real-world data are available on patients who continue the same biologic after incomplete remission at 12 months. We evaluated longitudinal remission trajectories in patients with severe T2-high asthma continuing the same biologic therapy. Methods: This retrospective real-world single-center SANI cohort included adults with severe asthma treated with one biologic agent and followed for at least 18 months. Clinical outcomes and remission status were assessed at 12 and 18 months according to the SANI definition, distinguishing complete remission, partial remission, and no remission. Results: The cohort included 146 patients; 64.4% were female, median age was 61 years, and all had a T2-high phenotype. Maintenance oral corticosteroid use decreased from 83.6% at baseline to 6.8% at 18 months, while symptomatic patients decreased from 100.0% to 11.0%. Median ACT improved from 12.0 to 22.0, and patients with ≥1 exacerbation decreased to 4.1% at 18 months. Complete remission increased from 36.3% at 12 months to 67.1% at 18 months, while no remission decreased from 54.1% to 16.4%. Among patients not in remission at 12 months, 43.0% achieved complete remission and 26.6% achieved partial remission at 18 months. Baseline oral corticosteroid use was associated with lower remission likelihood, whereas preserved baseline FEV1 favored remission at 18 months. Conclusions: Among patients with severe T2-high asthma selected for continuing an unchanged biologic for at least 18 months, remission status was more favorable at 18 months than at 12 months. This observation describes the trajectory of biologic continuers and should not be generalized to all patients who remain outside remission at 12 months. Because patients who discontinued or switched biologics were excluded, these data do not establish that continuation is preferable to switching after an incomplete 12-month response.